2021
DOI: 10.1186/s13223-021-00587-6
|View full text |Cite
|
Sign up to set email alerts
|

The extract of black cumin, licorice, anise, and black tea alleviates OVA-induced allergic rhinitis in mouse via balancing activity of helper T cells in lung

Abstract: Background A formulation of black cumin (Nigella sativa L.), licorice (Glycyrrhiza glabra L.), anise (Pimpinella anisum L.) and tea (Camellia sinensis (L.) Kuntze) (denoted BLAB tea) is traditionally used to relief allergy reaction including allergic rhinitis. However, little is known about its underlining mechanism of anti-allergic effects. Methods To investigate the anti-allergenic mechanism of BLAB tea, we treated ovalbumin (OVA)-induced allergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In PM 2.5 -induced BEAS-2B and HepG2 cells, anethole ( 40 ) reduced the levels of IL-6 and IL-8 by 96% and 87%, respectively, demonstrating it is a natural therapeutic agent to counteract PM-induced inflammation [ 108 ]. Recently, based on analysis of ovalbumin (OVA)-induced allergic rhinitis (AR) model mice, C. S. Liao’s team found that the anti-inflammatory response of BLAB tea containing P. anisum was relevant to the suppression activity on the accumulation of inflammatory cells and the release of Th2 and histamine in the nasal mucosa, NALF, and serum, and induction of the production of Th1 and Treg [ 109 ]. Another P. anisum study [ 9 ] indicated that polysaccharide extract mediated anti-inflammatory effects by improving edema and reducing MDA and SOD levels of oxidative stress indexes in muscle in carrageenan-induced foot swelling in mice.…”
Section: Pharmacologymentioning
confidence: 99%
“…In PM 2.5 -induced BEAS-2B and HepG2 cells, anethole ( 40 ) reduced the levels of IL-6 and IL-8 by 96% and 87%, respectively, demonstrating it is a natural therapeutic agent to counteract PM-induced inflammation [ 108 ]. Recently, based on analysis of ovalbumin (OVA)-induced allergic rhinitis (AR) model mice, C. S. Liao’s team found that the anti-inflammatory response of BLAB tea containing P. anisum was relevant to the suppression activity on the accumulation of inflammatory cells and the release of Th2 and histamine in the nasal mucosa, NALF, and serum, and induction of the production of Th1 and Treg [ 109 ]. Another P. anisum study [ 9 ] indicated that polysaccharide extract mediated anti-inflammatory effects by improving edema and reducing MDA and SOD levels of oxidative stress indexes in muscle in carrageenan-induced foot swelling in mice.…”
Section: Pharmacologymentioning
confidence: 99%